Key Diagnostic Finding in a Condition with Variable Clinical Presentations. (5th August 2013) - Sukumaran, Anju; Buchlis, John
Abstract : This is an interesting case series on a very common genetic condition which are often diagnosed late as clinical signs are inconspicuous. We would like to highlight the principal clinical examination finding which led to diagnosis.